Study of English Reading Instructional Design in Senior High School Based on the Activity-based Approach to English Learning - Zheng, You (Scientific Journal of Technology, 2025)
The perspective of English learning activities provides significant support for achieving the educational goal of core competence and also offers theoretical guidance for the practical teaching of front-line English teachers. The understanding of the concept of English learning activities by high school English teachers and the degree of alignment with the implementation of this concept have a significant impact on the effectiveness of classroom teaching and further influence the new progress of curriculum reform. The learning activities based on the perspective of English learning activities have the special connotation of “integrating six elements”, which is of great significance to the development of both teachers and students. To implement the activity-based view of English learning, teachers need to follow four fundamental concepts: consistently emphasizing “meaning exploration”, conducting “text interpretation” well, ensuring that “activity design” is logical, and making “goals of the activity” oriented towards competence. These concepts are illustrated in the reading teaching design of Unit 1, A Student of African Wildlife, in the compulsory volume 4 of the People's Education Edition of high school English textbooks.